SOIL-TRANSMITTED HELMINTH INFECTIONS IN HONDURAS: MAPPING INFECTION PREVALENCE AND IMPLICATIONS FOR HEALTH CARE REGIONALIZATION - Sturrock, Shelby (My University, 2017)
Soil-transmitted helminth (STH) (A. lumbricoides, T. trichiura and hookworm) infections are a significant public health concern in Honduras. These infections are treatable using inexpensive anthelmintic medications, however long-term control and eradication will require large investments in public and private sanitation infrastructure. Importantly, both types of interventions are targeted towards high-risk populations and regions rather than individuals. The goal of this thesis is to contribute to improving the efficiency of soil-transmitted helminth control efforts in Honduras. In our first study, we use multiple regression analyses to identify determinants of STH infections and generate estimates of A. lumbricoides, T. trichiura and hookworm infection prevalence, as well as recommended deworming frequencies, for each of Honduras’ 298 municipalities. Our estimates suggest that prevalence of all three infections has declined over time, however 75% of municipalities still require annual or semi-annual deworming. In our second study, we quantify how the type of region used for measuring prevalence and allocating resources can impact the success and efficiency of public health programs. More specifically, we compare administrative regions to alternative zoning schemes at the same geographic scale. Our findings suggest that regions designed to be homogeneous with respect to prevalence can be more efficient than existing municipalities (at the same scale) for distributing resources. This research has implications on future control efforts.
Keywords: Soil-transmitted helminth infections; Health care regionalization; Epidemiology; Honduras